The Effect of Athletic Mental Energy on Psychological Skills and Attitudes toward Soccer - Ahmet İslam (Journal of Educational Issues, 2024)
For optimal performance in soccer, high-level technical, tactical, and physical competencies are required, but they are not enough. Research shows that successful athletes apply psychological skills for high performance and need the presence of psychological aspects in sports. In this context, in addition to physical characteristics in soccer, psychological aspects should also be at a high level and in a solid structure. Therefore, the training of mental processes is very important in soccer. This paper explored whether soccer players’ athletic mental energy (AME) mediated their psychological skills in soccer (PSIS) and attitudes toward soccer (ATS). It established a hypothetical model examined by means of the Sobel test. The sample was composed of 295 soccer players from the Turkish 2021-22 soccer leagues. Data were collected using a personal information form, the Soccer Psychological Skills Scale-16 (SPSIS-16), the Soccer Attitude Scale (SAS-26), and the Athletic Mental Energy Scale (AMES). Participants’ ATS were positively correlated with their AME and PSIS. Their AME was positively correlated with their PSIS. Moreover, AME mediated PSIS and ATS. The findings verified the model. Trainers and coaches must brief soccer players about the relationship between AME, PSIS, and ATS. The theoretical model will bring innovation to the field of sports sciences, pave the way for further research, and will contribute to the literature.